2012
DOI: 10.1590/s0080-62342012000500024
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade pós-neonatal no território brasileiro: uma revisão da literatura

Abstract: RESUMOO presente trabalho trata-se de revisão sistemá ca, referente ao período de 2004 a 2009, sobre o tema mortalidade pós-neonatal. Teve o obje vo de iden fi car como se colocam na literatura, as causas da morte e a relação com as condições socioeconômicas. Foram selecionados 27 ar gos, 74,4% publicados em periódicos da área da Saúde Pública e 66,7%, de desenho do po ecológico. Quase a totalidade versava sobre grupos de causas e seus componentes (66,7%), seguidos pelo terço restante, sobre a iden fi cação do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
5
0
2
Order By: Relevance
“…Our results are in accordance with other systematic reviews. Ferrari [ 44 ] reported that life conditions according to socioeconomic indicators such as income, housing, basic sanitation, and accessibility to health were identified as determinants of post-neonatal deaths. This review also highlighted the existence socioeconomic inequalities in the North and Northeast regions impacting on infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with other systematic reviews. Ferrari [ 44 ] reported that life conditions according to socioeconomic indicators such as income, housing, basic sanitation, and accessibility to health were identified as determinants of post-neonatal deaths. This review also highlighted the existence socioeconomic inequalities in the North and Northeast regions impacting on infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although poverty and social vulnerability are already known in the most historically underdeveloped regions of the country, such as the Northeast region, the prevalence of FNI has been spatially correlated with infant mortality in these territories, as corroborated by the findings of this research, show that besides social inequalities already known, inequalities are found in material, biological, psychosocial and behavioral health-producing factors that affect child health 44 . Studies show that the occurrence of FNI is associated with breastfeeding for less than 24 months 31 , exclusive breastfeeding for less than six months 31 , childhood asthma 45 , child malnutrition 46 , reduced energy, protein and iron consumption by the child 47 and the worst situations of child nutritional status, such as weight, height and weight-for-age deficits 30 .…”
Section: Discussionmentioning
confidence: 99%
“…They reflect the environment, nutritional and well-being conditions in which this population is inserted. In this component of the IMR, government actions, such as basic sanitation, income distribution, and a greater supply of medical services, have a greater impact on their reduction, especially when they include less favored social classes 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%